Catheter-associated bloodstream infections in adults with cancer: a prospective randomized controlled trial. Issue 2 (October 2020) - Mollee, P.; Okano, S.; Abro, E.; Looke, D.; Kennedy, G.; Harper, J.; Clouston, J.; Van Kuilenburg, R.; Geary, A.; Joubert, W.; Eastgate, M.; Jones, M.
Summary: Background: A common complication of central venous access devices (CVADs) is catheter-associated bloodstream infection (CABSI). We previously demonstrated that insertion of CVADs on the right side was associated with increased risk of CABSI, and hypothesized that this related to the predominance of right-handedness in the patient population, resulting in greater movement and bacterial contamination. Aim: To perform a prospective randomized, controlled, non-blinded study to determine whether the side of CVAD insertion influenced the incidence of CABSI. Methods: Adult cancer patients were randomly allocated to either dominant or non-dominant side CVAD insertion. The primary endpoint of the study was the number of line-days until CABSI, determined in a blinded fashion by two assessors. Findings: In all, 640 CVADs were randomized to dominant ( N = 322) or non-dominant ( N = 318) side of insertion, 60% had haematological malignancies, and 40% solid tumours. CVADs were a peripherally inserted central catheter line (67%), tunnelled CVAD (23%), and non-tunnelled CVAD (10%). Twenty-two percent of CVADs were complicated by CABSI. The rate of CABSI per 1000 line-days was 3.49 vs 3.66 in the non-dominant vs dominant group (hazard ratio (HR): 0.91; 95% confidence interval (CI): 0.65–1.28). By multivariable analysis, the rate of CABSI was increased by: use of tunnelled CVADs compared to peripherally inserted central venous catheter lines (HR: 2.05; 95% CI: 1.45–2.91); having a haematological malignancy compared to non-gastrointestinal solid tumours (5.55; 2.47–12.5); but not dominant compared to non-dominant side of CVAD (0.97; 0.69–1.36). Conclusion: CABSI in adult patients with cancer was not impacted by whether CVAD insertion was on the dominant or non-dominant side.